(untitled) (European Journal of Health Research, 2017)
The objective of this study was to identify the relationship between sociodemographic aspects and the quality of life in retirees of the Mexican Institute of Social Security of Zacatecas, for this a correlational descriptive study was carried out in a sample of 140 retirees, 90 women and 50 men with an average age of 61.23 years. The WHOQOL-BREF WHO scale (Espinoza, Osorio, Torrejón, Lucas-Carrasco y Bunout, 2011) was used to measure Quality of Life, and a questionnaire with sociodemographic and psychosocial data was applied to obtain the profile of the population. Among the results, significant and negative correlations appear between the perception of Quality of Life and variables such as retirement age and physical activity. As well as significant differences in variables such as the presence of chronic diseases, physical activity, eating habits and type of housing. In conclusion, it is emphasized that the perception of quality of life in the sample of retirees is determined by sociodemographic aspects and health habits that are areas of opportunity in the understanding of the phenomenon and the establishment of strategies that favor the adaptation to the process of retirement.